Some features of mathematical education in Lithuania during the years of dependence - Banionis, Juozas (Lietuvos matematikos rinkinys, 2004)
With Lithuania’s incorporation in the USSR strictly limited system of soviet education was introduced in the country. This type of educationhad already been functioning since 1935. At that time curriculums of secondary school emphasized the necessity to educate pupils’ logical thinking, vivid imagination of space. In V–XI forms mathematics as a subject consisted of systemic arithmetic, algebra, geometry and trigonometry courses, which were sufficient for students entering the institutions of higher education. Starting with the year 1954 the USSR changed the structure of secondary education and revised the content and methods of teaching mathematics. One of newly created requirements was aimed at applying mathematical basic knowledge in practice and in teaching other subjects. Composing of mathematical functions was emphasized as one of priorities which was tried to make related with real processes. In the middle of the 7th decade creation of new educational programme was started in the USSR. A. Kolmogorov under the influence of the ideas of 1959 Reimont conference started implementation of theoretical positions of mathematical sets into curriculum of secondary school and treated transformations as the basics of geometry at school. At the beginning of the 9th century the syllabi of geometry were changed gradually. New syllabus of mathematics finally spread in Lithuania in 1987/1988. The aim of the started reform was to specify the content and scope of teaching subjects, eliminate some material from overburdened textbooks, to identify optimal scope of competence and skills according to a subject of every form at school. In general, in the new syllabus of mathematics, which was formed in the 7th–9th decade, mathematics at school was set closer to modern notion of mathematics as a science.